2001
DOI: 10.1002/1097-4598(200101)24:1<130::aid-mus20>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response before and after surgical release of carpal tunnel syndrome

Abstract: Sympathetic skin response (SSR) was performed before and 1 year after surgical release of the median nerve in 20 subjects (mean age 52.8 years) with unilateral idiopathic carpal tunnel syndrome (CTS). SSR was evoked by stimulation of the ulnar nerve at the wrist contralateral to the side with CTS, recording from the palm, third (M3) and fifth fingers, and from the third finger contralateral to the side of CTS (M3c). Before surgery, anomalies of M3 SSR were found in 8 hands (40%): M3 SSR was absent in 1 hand; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…35 Contrarily, Mondelli et al reported that the absence of postoperative improvement of sympathetic skin properties following CTR might be due to the poor reinnervation capacity of the sympathetic fibers after long-term degeneration. 36 The results of changes in skin's sympathetic response after CTR seem to vary, but alterations in the skin's property might influence the friction response between the finger pad and the grasped object. Considering that skin friction might be a critical factor affecting force production during pinch, a limitation of our study is its lack of measurement and representation of changes in skin frictional properties of patients before and after CTR.…”
Section: Discussionmentioning
confidence: 99%
“…35 Contrarily, Mondelli et al reported that the absence of postoperative improvement of sympathetic skin properties following CTR might be due to the poor reinnervation capacity of the sympathetic fibers after long-term degeneration. 36 The results of changes in skin's sympathetic response after CTR seem to vary, but alterations in the skin's property might influence the friction response between the finger pad and the grasped object. Considering that skin friction might be a critical factor affecting force production during pinch, a limitation of our study is its lack of measurement and representation of changes in skin frictional properties of patients before and after CTR.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated autonomic dysfunction in CTS and most of these have looked at the sudomotor nerve fibres, using the sympathetic skin response (Kanzato et al, 2000;Mondelli et al, 2001;Reddeppra et al, 2000;Sener et al, 2000). They have shown autonomic dysfunction in 40 to 77% of CTS patients.…”
Section: Article In Pressmentioning
confidence: 99%
“…When onset potential was shallow, the recorded trace (x2-x8) was further amplified to pinpoint the exact onset of SSR. These methods have been reported elsewhere [20].…”
Section: Sympathetic Skin Responsementioning
confidence: 87%